2010
DOI: 10.1007/s10694-010-0189-2
|View full text |Cite
|
Sign up to set email alerts
|

Firefighter Turnout Gear Durability Study—Evaluation of Visibility Trim

Abstract: Abstract. The high visibility trim requirements for NFPA 1971for NFPA (2007 turnout gear are intended to provide the user conspicuity enhancements in both daytime and nighttime environments. This study evaluated the reflectance, color and fluorescence properties of high visibility trim on firefighters used turnout gear. Forty-four used garments, grouped in age categories from 2 to 10 years (retired), were visually evaluated according to the Section 4 of the NFPA 1851-Advanced Inspection Checklist. Advanced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The manufacturer of the fabric attributed the problem to repeated heat damage experienced by the garment, which should have led to the garment being taken off service 16 . In addition, studies conducted on used firefighters' protective clothing, some of them still in use, have evidenced reductions in the turnout gear's performance over time 17–21 . For instance, 65.7% of the less than 10‐year‐old moisture barriers evaluated failed to meet the water penetration requirement set by the National Fire Protection Association (NFPA).…”
Section: Introductionmentioning
confidence: 99%
“…The manufacturer of the fabric attributed the problem to repeated heat damage experienced by the garment, which should have led to the garment being taken off service 16 . In addition, studies conducted on used firefighters' protective clothing, some of them still in use, have evidenced reductions in the turnout gear's performance over time 17–21 . For instance, 65.7% of the less than 10‐year‐old moisture barriers evaluated failed to meet the water penetration requirement set by the National Fire Protection Association (NFPA).…”
Section: Introductionmentioning
confidence: 99%
“…[16] standard. [17][18][19][20][21] What is more worrisome is that in some instances, a major loss in performance can occur before a clear visual indication of fabric aging. 22 Investigations on the accelerated aging of highperformance fiber-based fabrics have been conducted by researchers to determine the consequences of aging on performance, degradation mechanisms, and kinetics.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In a series of studies conducted at the University of Kentucky on firefighters' suits used in fire stations from 2 to 21 years, the researchers measured severe loss in the outer shell fabric performance. [10][11][12][13][14] They observed that 10% of the outer shells tested that were 4 years old or less did not pass the mechanical performance requirements of the National Fire Protection Association (NFPA)'s NFPA 1971 specification. 15 In addition, 65% of the moisture barriers tested did not meet the NFPA 1971 15 requirements for water penetration.…”
Section: Introductionmentioning
confidence: 99%